2008
DOI: 10.1111/j.1747-0765.2008.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Land-use impact on soil carbon, nitrogen, neutral sugar composition and related chemical properties in a degraded Ultisol in Leyte, Philippines

Abstract: Over the past several decades, the conversion of native forest to agricultural land use has accelerated and featured in the development of Philippine landscapes. This study evaluated the effect of land-use change on soil carbon, nitrogen, neutral sugar composition and other related soil chemical properties in a degraded soil (Typic Hapludult) in Leyte, Philippines. Using a space-for-time substitution (paired-area) approach, soil samples were collected and examined from secondary forest (SF), mahogany plantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 23 publications
3
22
0
1
Order By: Relevance
“…Owing to the effect of complicated soil‐forming factors and human activities, SOC exhibits high spatial variability (Matsumoto et al. 2008; Navarrete and Tsutsuki 2008; Zhang et al. 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the effect of complicated soil‐forming factors and human activities, SOC exhibits high spatial variability (Matsumoto et al. 2008; Navarrete and Tsutsuki 2008; Zhang et al. 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Conversion of PF to other land uses has led to a decrease in FAs (Table 1), which was more appreciable at the RF and GR sites under intensive cultivation (Navarrete and Tsutsuki 2008). In contrast, the HA contents in the soils were small even in the PF.…”
Section: Discussionmentioning
confidence: 99%
“…There have been very few studies examining the effect of land use on humus composition in the Philippines (e.g. Navarrete and Tsutsuki 2008; Ohta 1990). Ohta (1990) reported that conversion of forest into grassland (GR) has resulted in a considerable decrease in soil organic C, humic acids (HAs) and fulvic acids (FAs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some neutral sugars that are associated with the soil mineral matrix (i.e., bound to iron and aluminum oxides) are resistant to biodegradation as documented in Andosol [6,14,36,37] and Acrisol [14]. Although the amount of mannose was not statistically different between HiFA and HoFA, the slightly higher mannose in HoFA suggest that mannose is relatively stable against microbial decomposition.…”
Section: Amount and Composition Of Neutral Sugarsmentioning
confidence: 98%